Character recognition and inspection - Pang, Yuen Lai. (2008)
In this project, a software application is developed with image processing techniques and neural network to check the text on the IC chip. By using optical character recognition (OCR) in this software, we increased the flexibility of IC chip inspection because allowances can be made to cater to different characters on the chip. As compared to the traditional approach of template matching, the suggested solution eliminates the storing of numerous sets of markings associated to different sets of characters that can appear on the same IC chip.